2005
DOI: 10.1002/jcp.20442
|View full text |Cite
|
Sign up to set email alerts
|

The non‐proteolytically active thrombin peptide TP508 stimulates angiogenic sprouting

Abstract: Thrombin is a serine protease that promotes platelet aggregation, blood coagulation, and tissue repair. A peptide derived from a non-proteolytically active region of thrombin, TP508, also promotes tissue repair and increased vascularity, yet does not activate platelet and inflammatory cascades. TP508 binds to cells with high affinity and stimulates cells independent of the proteolytically active thrombin receptors (PARs) and thus is considered to activate a non-proteolytically active receptor (non-PAR) pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…Angiogenic growth of MVF in collagen gels is characterized by the formation of smooth vascular sprouts that are morphologically distinct from the rough, smooth muscle-associated appearance of the parent vessel (15,28,38). The sprouting assay has been described previously (38).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenic growth of MVF in collagen gels is characterized by the formation of smooth vascular sprouts that are morphologically distinct from the rough, smooth muscle-associated appearance of the parent vessel (15,28,38). The sprouting assay has been described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…MVF were isolated from male SpragueDawley rats as previously described (28,38), with slight modifications. Briefly, after rats were killed, epididymal fat pads were collected, minced, and digested in a collagenase solution (2 mg/ml in PBS containing 0.1% BSA) for 8 -10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TP508 has previously been shown to stimulate tissue revascularization following injury [7,8,10,12,20] and angiogenic sprouting in ex vivo cultures of microvessel fragments [21]. Recent in vivo and long-term culture experiments showed that TP508 reverses endothelial dysfunction and increases NO production in endothelial cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, the process of new blood vessel formation from preexisting ones, is comprised of several discrete steps including dissociation of matrix, endothelial cell migration, proliferation and tube differentiation [19]. TP508 stimulated early revascularization in dermal and bone injury models [7,8,10,12,13,20], and stimulated vascular sprouting in ex vivo cultures of microvessel fragments [21]. Thus, TP508 effects on tissue repair appear to be linked to its stimulation of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%